TINGKAT KEMAMPUAN Vo2Max PADA ATLET TENIS MEJA PUTERA PRAPON RIAU - Ruqayah, Roiyatul; Nabila, Restu (Dharmas Education Journal (DE_Journal), 2024)
The aim of this research is to see the level of Vo2Max ability of PRAPON Riau men's table athletes. This research is quantitative descriptive research with the research method being a survey method, namely data collection using only tests and measurements. The subjects in this research were 8 men's table tennis athletes from PRAPON Riau. The sampling technique used total sampling in which the entire population was taken as a sample. The data analysis technique in this research is descriptive statistics to collect, present and determine values. The results of the research show that from the results of research data that has been carried out by researchers, the Vo2Max ability of male PRAPON Riau table tennis athletes using the 15 minute Balke test instrument on male PRAPON Riau athletes, totaling 8 athletes, had the highest Vo2Max value of 52.89 and the lowest 49.88. The overall average Vo2Max ability level of PRAPON Riau male athletes is 51.17 which is in the medium category. Based on the data that has been obtained, it is concluded that the Vo2Max level of male PRAPON Riau table tennis athletes is in the medium category.